Pengaruh Motivasi Kerja Kepemimpinan dan Beban Kerja terhadap Kinerja Pegawai Kantor Camat Batang Angkola Kabupaten Tapanuli Selatan - Lanniari Hasibuan; Roni Artha Lumbantobing; Gusti Oloan Siregar; Gusni Armi Pasaribu (Jurnal Prodi Fakultas Ekonomi-UISU, 2022)
Problem this study is how influence job motivation on employee’s performance. How influence leadership on employee’s performance. How influence work load on employee’s performance. How influence job motivation, leadership and work load on employee’s performance. The purpose this study to determine and analyze the effect job motivation on employee’s performance. Determine and analyze the effect leadership on employee’s performance. Determine and analyze the effect work load on employee’s performance. Determine and analyze the effect job motivation, leadership and work load on employee’s performance. Sample in the study is 34 employee’s. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results the study indicate job motivation variable has a positive and significant effect on employee’s performance. Leadership variable has a positive and significant effect on employee’s performance. Work load variable has a positive and significant effect on employee’s performance. Job motivation, leadership and work load variable has a positive and significant effect on employee’s performance.